SEJARAH PERKEMBANGAN FILSAFAT ILMU KLASIK PERTENGAHAN MODERN DAN KONTEMPORER: sejarah perkembangan filsafat ilmu klasik pertengahan modern dan kontemporer - ardhanun, sekar; razaq, Abdur; imron, kristina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the historical development of the philosophy of sciencefrom the classical, medieval, modern, to contemporary periods, as well as toexamine the contribution of each period in shaping contemporary scientificparadigms. This study is based on the understanding that the philosophy of sciencecannot be separated from the dynamics of human intellectual history and the social,cultural, and intellectual contexts surrounding it. The research employs a libraryresearch method with a historical-philosophical approach through comparativeanalysis of the thoughts of philosophers and key works in the philosophy of scienceacross different historical periods. Data are obtained from relevant academicliterature, including books and scholarly journal articles. The findings indicate thatduring the classical period, the philosophy of science emphasized the search for theessence of knowledge through rationality and logic as the foundation of scientificinquiry. The medieval period was characterized by a synthesis of Greek philosophyand theological traditions in both Islamic and Christian thought, resulting in anunderstanding of knowledge as a unity of reason and revelation. The modern periodmarked a significant shift toward rationalism, empiricism, and the development ofscientific methods based on observation and experimentation, leading to theseparation of philosophy from science. Meanwhile, the contemporary period ischaracterized by criticism of positivism, the emergence of methodological pluralism,and critical reflections on ethical, social, and cultural dimensions of scientificpractice. This study concludes that the development of the philosophy of science isdynamic and contextual, making historical understanding essential for building acritical and reflective scientific framework.